PENGARUH PEMANFAATAN KOLEKSI BAHAN PUSTAKA TERHADAP PRESTASI BELAJAR SISWA DI SMA NEGERI 1 JUNJUNG SIRIH - Febriani, Fadiya; Marlini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of library collection utilization on students’ learning achievement at SMA Negeri 1 Junjung Sirih, Solok Regency. The research was motivated by the low frequency of students visiting the school library despite the adequate availability of library collections. This research employed a quantitative approach with a descriptive method. The population consisted of 480 students, while the sample comprised 83 respondents selected through simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed using validity, reliability, and simple linear regression tests. The results indicated that the level of library collection utilization was in the moderate category, while students’ learning achievement was in the high category. The regression analysis revealed a positive and significant influence between the utilization of library collections and students’ learning achievement. Thus, the higher the level of library collection utilization, the better the students’ academic performance. This finding emphasizes the importance of optimizing the role of school libraries as learning resource centers to enhance students’ academic quality.